Arsenate Impact on the Metabolite Profile, Production, and Arsenic Loading of Xylem Sap in Cucumbers (Cucumis sativus L.) - Uroic, Kalle; Salaun, Pascal; Raab, Andrea; Feldmann, Jörg (Frontiers in Physiology, 2012)
Arsenic uptake and translocation studies on xylem sap focus generally on the concentration and speciation of arsenic in the xylem. Arsenic impact on the xylem sap metabolite profile and its production during short term exposure has not been reported in detail. To investigate this, cucumbers were grown hydroponically and arsenate (AsV) and DMA were used for plant treatment for 24 h. Total arsenic and arsenic speciation in xylem sap was analysed including a metabolite profiling under arsenate stress. Produced xylem sap was quantified and absolute arsenic transported was determined. AsV exposure has a significant impact on the metabolite profile of xylem sap. Four m/z values corresponding to four compounds were up regulated, one compound down regulated by arsenate exposure. The compound down regulated was identified to be isoleucine. Furthermore, arsenate has a significant influence on sap production, leading to a reduction of up to 96 % sap production when plants are exposed to 1000 μg kg-1 arsenate. No difference to control plants was observed when plants were exposed to 1000 μg kg-1 DMA. Absolute arsenic amount in xylem sap was the lowest at high arsenate exposure. These results show that AsV has a significant impact on the production and metabolite profile of xylem sap. The physiological importance of isoleucine needs further attention.